Lung cancer detection and classification using machine learning - Arefin, Mahbubul; Hekim, Md. Lokman; Farjana, Afia; Bala, Nisarga (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.